The advertisements of beauty products for black women as deracialized speech in emphasis on the circulation of speeches - Pereira, Francineide Dourado; Nascimento, Maria da Graças Lessa; Lima, Marta Maria Chaves (Seven Editora, 2023)
This article aims to point out the existence of deracialized discourses contained in advertisements of feminine beauty products for black women, mainly hair products. The analysis will be based on advertisements for salon line hair, because it contains discourses of identity and representativeness and visually in its advertisements learn speeches such as "empowerment". The study is based on Modesto’s (2021) Deracialized discourses and Orlandi (1999) Discourse analysis: principles and procedures. The methodology at first consists of collecting two advertisements of the aforementioned brand that circulate in alternative media. It is expected that this research will collaborate with the questioning of discourses of race. Such questioning is more widely discussed outside, while in Brazil there is a payment due to the false idea of "Brazil of football and samba" for the elite, however for the poor and black periphery occurs the opposite with the deracialization of large mass media regarding everything that refers to education, security, health, leisure, and urbanization. DOI: https://doi.org/10.56238/methofocusinterv1-088